Avaliação de orientações sistematizadas de enfermagem no pós-operatório de mulheres submetidas à mastectomia - Melo, Elizabeth Mesquita (2007)
It is emphasized the importance of nursing attendance in the post-operatory of mastectomy aiming the identification of problems for women’s life quality and minimization of physical and psychological alterations, so that they have a better readaptation to social environment. The study had as its general objective to evaluate the contribution of nursing assistance developed in the post-operatory for physical, emotional and social readaptation of mastectomized women. The specific objectives were: to identify differences in physical, social and emotional responses among women who were submitted or not to nursing systematized orientation; to know the post-operatory complications present in the two groups of women; and to identify in the groups doubts related to necessary care to prevent complications after the mastectomy. It is an experimental study, a randomized controlled clinical essay. An intervention was applied in a group of women (group intervention) in the immediate post-operatory of mastectomy to observe its effects, in relation to the other group in which the intervention was not carried out (group control). The data was collected between November, 2005 and March, 2006 in an institution which is specialized in oncology, Fortaleza-Ceará. The population was composed of holders of breast diseases who were submitted to surgeries during this period, and was composed of 80 women, 40 in each group, selected at random. The data was organized and analyzed quantitatively and submitted to statistical analysis. The Program Microsoft Office Excel 2003 was used for the data bank. The significance level of the tests was considered equal to 5%. The Project was approved by the ethical committee of the institution. The predominant age group was 36 to 68 years old (87,5%); 60% came from the state countryside. 57,5% were married. The modified radical mastectomy with axillary dissection was the most common procedure (56%) and the most common diagnosis was infiltrating ductal carcinoma (58,8%). It was identified significative statistical difference concerning manifestation of abandonment, lack of vigor, feeling of tiredness and tension, with an indicator of emotional alteration lower in the group intervention. 57,5% of the group intervention, after the surgery, restarted activities which helped in the recuperation, what was observed in only 7,5% of the group control. Doubts about the activities were manifested by 57,5% of women from the group control and 37,5% from the group intervention. There were more surgery complications in the group control (92,5%) in relation to the group intervention (57,5%). This group presented less difficulty to use the suction drain (7,5%), being 31,6% in the group control. The attendance directed to the group intervention contributed to the adoption of positive attitudes towards the care with the arm from the operated side. The nursing systematized orientation in the post-operatory of mastectomy has inestimable value, considering it provides elucidation of doubts about the disease and the surgery, and makes possible the adoption of care which is favorable to women’s faster recuperation and to their readaptation.